Do discurso ao diálogo: interfaces fisico-digitais no espaço urbano para a retomada da esfera pública - Guilherme Ferreira de Arruda (2014)
This masters thesis aims to propose an urban digital interface in Catas Altas, Minas Gerais, considering informations and communications technologies (ICTs) potential to contribute to the resumption of the public sphere. For the philosopher Hannah Arendt, resume public sphere means articulaste individuals so they can act politicaly, as citizens. To experience this possibility, the interface production process proposes the formation of a network of plural relations (to ensure that the different perspectives of citizens are considered in decision), dialogic (to ensure the creation of new information, bringing possible changes to the community) and on matters of public interest (away from the social sphere, in which private interests define the political decisions). To build the framework of the interface produced in Catas Altas five interfaces with potencial for the resumption of the public sphere were analyzed: three of them are digital and two are physical--digital. After the analyzes, it was evident the importance of including the population since the beginng of the process. Only then issues relevant to the community can be used in the interface design process in order to facilitate the engagement of residents. To support the design of the interface, participatory activities with the community were held over ten months, such as photography and video workshops and movie screenings in the streets. R.I.C.A. (Catas Altas Ideas Network) was developed as a prototype itinerant and proposes socio--spatial discussions from an LED panel. This LED panel is attached to a city map. People can interact with the map, lighting parts and finding positive or negative points with bright little balls. The results of the interaction of locals with the map are published on the internet, showing the reviews on various urban issues. After a trial period, it became evident that the fact that R.I.C.A. is itinerant in public space, based on the city map and especially for being contextualized with the reality of the city contributed to the interaction of people from different social classes and circles, talking exclusively about the socio--spatial complexities of Catas Altas. Thus, R.I.C.A. proved successful in articulating the residents around public interest issue, away from the social sphere and pointing possible directions for the resumption of the public sphere.